Habit Formation and Health Benefits of Regular Exercise Among Physically Inactive Populations in the Context of National Fitness Promotion - Hang Gao (Studies in Sports Science and Physical Education, 2026)
Physical inactivity is a common health-related behavior and is often linked with long periods of sitting, irregular exercise, and a clear gap between exercise intention and actual participation. For physically inactive populations, the main difficulty is not only starting exercise but maintaining it long enough to form a stable habit. This paper discusses the main barriers to regular exercise, including weak motivation, high perceived cost, unrealistic exercise goals, and the lack of stable exercise cues and supportive environments. It then examines how regular exercise habits can be developed through low-threshold participation, suitable activity choices, fixed daily routines, positive feedback, and repeated behavior. The paper also discusses the health benefits of regular exercise, including improvements in physical fitness, metabolic health, sleep, emotional well-being, and daily functional capacity. Greater attention should be given to long-term adherence rather than short-term exercise volume. Exercise plans need to match individual ability, daily schedules, and physical condition so that physical activity can become a stable part of everyday life.